Jenis Intervensi Pada Pasien Dengan Perilaku Kekerasan Di Rumah Sakit Jiwa Scoping Review - Kurniawan, Bayu Eka; Dwidiyanti, Meidiana; Erawati, Meira (Universitas Tribhuwana Tunggadewi, 2024)
Violence behaviour poses a potential risk of physical harm to oneself or others. Violence behaviour must be promptly addressed by providing intervention to avoid detrimental impacts on the patient, others, or the surrounding environment. This research aims to identify the types of interventions for patients with violent behaviour in psychiatric hospitals. This review adopts a scoping review approach, following the analysis procedure by Arksey and O'Malley. Articles were identified using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) method. Inclusion criteria for this review article include English or Indonesian language articles, original articles, articles using quantitative, qualitative, and mixed research methods published within the last 5 years. From the review results of 1.128 articles, 8 articles met the inclusion criteria. The analysis results indicate various types of interventions proven to be effective in reducing violent behaviour in patients in psychiatric hospitals. Treatments involving physical, psychological, and belief-based activities are suitable for reducing violent behaviour in patients in psychiatric hospitals. Furthermore, to determine the real impact of reducing violent behaviour, supplemental research is needed to develop interventions in patients in psychiatric hospitals.